Emerging Novel Drug Delivery System for Control Release of Curcumin through Sodium Alginate/Poly(ethylene glycol) Semi IPN Microbeads-Intercalated with Kaolin Nanoclay - Sreekanth Reddy, O.; Subha, M.C.S; Jithendra, T.; Madhavi, C.; Chowdoji Rao, K. (Journal of Drug Delivery and Therapeutics, 2019)
The aim of the present work is fabrication of Curcumin encapsulated microbeads from Sodium Alginate/Polyethylene Glycol/Kaolin using glutaraldehyde as crosslinker by simple ionotropic gelation technique. The developed microbeads were characterized by Fourier transform infrared spectroscopy to confirm the formation of microbeads. Differential scanning calorimetry and X-ray diffraction studies have confirmed uniform molecular dispersion of CUR in the microbeads. Encapsulation efficiency of CUR in microbeads was ranged from 40 to 49%. Dynamic swelling studies and in vitro release kinetics were performed in simulated intestinal fluid (pH 7.4) and simulated gastric fluid (pH 1.2) at 37 oC. The results suggest that both swelling studies and cumulative release studies were depend on pH of the test medium, which might be suitable for intestinal drug delivery. The in vitro release data were analysed by using Korsmeyer peppas equation to compute the diffusion exponent (n); the results suggest that it followed non-Fickian diffusion.Keywords: Sodium Alginate, Polyethylene Glycol, Kaolin, Microbeads, Drug delivery